2013
DOI: 10.1093/cvr/cvt093
|View full text |Cite
|
Sign up to set email alerts
|

KATP channel opening accelerates and stabilizes rotors in a swine heart model of ventricular fibrillation

Abstract: Upon KATP-channel opening, VF consisted of rapid and highly organized domains mainly due to stationary rotors, surrounded by poorly organized areas. A 'beat phenomenon' due to the quasi-periodic onset of drifting rotors was observed. These findings demonstrate the feasibility of a VF driven by stable rotors in hearts whose size is similar to the human heart. Our model also showed that complex fractionation does not seem to localize stationary rotors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The effect of hyperkalemia on the period of spiral wave rotation was studied by [29] who obtained similar dependency but only for concentraions of larger than 8 mM. The same effect of hypoxia was investigated by [30] on canine ventricular slices and later by [31] on swine hearts. The results obtained in their experiments are in accordance with our simulations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The effect of hyperkalemia on the period of spiral wave rotation was studied by [29] who obtained similar dependency but only for concentraions of larger than 8 mM. The same effect of hypoxia was investigated by [30] on canine ventricular slices and later by [31] on swine hearts. The results obtained in their experiments are in accordance with our simulations.…”
Section: Discussionmentioning
confidence: 96%
“…The tendency for a fibrillation pattern to become more organized due to global ischemia was first demonstrated experimentally by [37] on rabbit hearts. In addition, a recent experimental study on the effects of hypoxia in swine hearts by [31] has also shown that activation of channels makes the fibrillation pattern more stable and stops rotors from meandering. However, a study by [26], performed also on swine hearts, argues that flattening of the restitution curve does favour VF termination, though, to achieve that flattening they used a potassium channel antagonist—bretylium—which has an effect opposite to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In nonischemic, cardiomyopathic Langendorff-perfused human hearts, glibenclamide was found to terminate ventricular fibrillation (VF) (218), leading to the concept that K ATP channel opening participates in the maintenance of VF. They may do so by stabilizing rotor dynamics during VF, as suggested from a study performed in pigs (650). Thus the stage is set for future studies to determine whether K ATP channel block may represent a viable therapeutic antiarrhythmic target.…”
Section: Continuedmentioning
confidence: 99%
“…6 Although the interaction of very stable high frequency sources (e.g. intramural scroll waves) can produce the onset of repetitive drifting rotors, 37 these differences most likely rely on the filtering methods in BSM/ECGI approaches and the extent of interpolation used in basket-catheter mapping. Thus, excessive interpolation/filtering or lack thereof may lead to differing conclusions about the actual stability of the sources driving AF.…”
Section: Controversies and Future Directionsmentioning
confidence: 99%